Lessons learned from 29 lymphoepithelial cysts of the pancreas: institutional experience and review of the literature. Issue 7 (July 2018) - Groot, Vincent P.; Thakker, Sameer S.; Gemenetzis, Georgios; Noë, Michaël; Javed, Ammar A.; Burkhart, Richard A.; Noveiry, Behnoud B.; Cameron, John L.; Weiss, Matthew J.; VandenBussche, Christopher J.; Fishman, Elliot K.; Hruban, Ralph H.; et al.
Abstract: Background: Lymphoepithelial cysts (LECs) are rare pancreatic cystic lesions. Since LECs are benign, preoperative diagnosis is important to differentiate from a cystic neoplasm and avoid unnecessary surgery. The aim of this study was to identify clinical, radiographic and cytopathologic features associated with LECs. Methods: A retrospective review was performed of patients diagnosed with LEC between 1995 and 2017 at our hospital. Clinicopathologic and radiographic imaging features were documented. Results: Of 29 patients with pancreatic LEC, 22 underwent surgical resection. The majority were male (n = 24) with a median age of 55 years (range, 21-74). During the evaluation, all patients underwent a CT, with endoscopic ultrasound (EUS) guided fine needle aspiration (FNA) biopsy (n = 22) and/or MRI/MRCP (n = 11) performed in a smaller number of patients. A combination of exophytic tumor growth on imaging and the presence of specific cytomorphologic features on the EUS-FNA cytology biopsy led to the correct diagnosis of LEC and prevention of unnecessary surgery in 7 patients. Discussion: Differentiating LECs from premalignant pancreatic cystic neoplasms remains difficult. Findings of an exophytic growth pattern of the lesion on abdominal imaging and the presence of specific cytomorphologic features in the EUS-FNA biopsy could help clinicians diagnose LEC preoperatively.